2022
DOI: 10.1186/s12887-022-03497-7
|View full text |Cite
|
Sign up to set email alerts
|

Fundamental motor skills of kindergarten children in different environments and ethnic groups in Northwest China

Abstract: Background The status of children’s early motor skills play an important role during childhood and across lifetime. This study described FMS proficiency among boys (n = 189) and girls (n = 179) kindergarten children from 3 to 6 years old (4.4 s 0.7, mean ± SD) in northwest China. The differences in FMS proficiency of boys and girls from different environments, ethnic groups were analyzed respectively. Methods TGMD-3 was used to assess FMS. FMS mast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Meanwhile, [24] shows that boys, on average, outperform girls when it comes to locomotor skills proficiency. A study by [25] found that when comparing the ability levels of boys and girls in hop, skip, and slide, the former group did better (p < .05). After searching extensively through academic literature, researchers were unable to locate any research that specifically addressed nonlocomotor skills.…”
Section: Discussionmentioning
confidence: 98%
“…Meanwhile, [24] shows that boys, on average, outperform girls when it comes to locomotor skills proficiency. A study by [25] found that when comparing the ability levels of boys and girls in hop, skip, and slide, the former group did better (p < .05). After searching extensively through academic literature, researchers were unable to locate any research that specifically addressed nonlocomotor skills.…”
Section: Discussionmentioning
confidence: 98%
“…FMS was assessed using the Test of Gross Motor Development-Third Edition (TGMD-3) which has been validated in China and has demonstrated satisfactory inter-rater (ICC = 0.87) and intra-rater reliability (ICC = 0.95) [ 51 ]. The TGMD-3 consists of two sub-scales: the locomotor skill sub-scale, which includes six skills (run, gallop, hop, horizontal jump, slide, and skip) (inter-rater = 0.83, intra-rater = 0.93), and the ball skill sub-scale, which includes seven skills (one hand forehand strike of a self-bounced tennis ball, kick a stationary ball, overhand throw, underhand throw, two hand strike of a stationary ball, one hand stationary dribble, and two hand catch) (inter-rater = 0.79, intra-rater = 0.93).…”
Section: Methodsmentioning
confidence: 99%
“…Sustainable Development Goal 4 within Education 2030 emphasizes the need for Sustainability 2024, 16, 1400 2 of 13 universal access to quality early childhood development, care, and pre-primary education, aiming at fostering holistic children's development, and ensuring that all children acquire the knowledge and skills needed to promote sustainable development [2]. However, most preschool children currently face at least three problems that pose a negative, long-term impact on their development: (1) physical inactivity [3], (2) poor fundamental movement skills (FMS) [4,5], and (3) inadequate preparation for school [6]. Meanwhile, childhood obesity and its associated health issues have garnered international attention.…”
Section: Introductionmentioning
confidence: 99%